Manajemen Laba Perspektif Al Muthaffifin - chairul iksan burhanuddin; Firman Syah (Akuisisi: Jurnal Akuntansi, 2022)
In the subject of accounting, earnings management is a major challenge, particularly when it comes to presenting financial statements. In practice, earnings management is carried out by managers in order to give information to top management for specific goals, such as bonus purposes. As a result, the information supplied by the manager to the management is incorrect. To provide a path out of this practice, a rebuilding is required. This study employs a qualitative method based on a critical paradigm. With the goal of presenting a fresh viewpoint on financial statement presentation. The findings of this study shed new light on the results of the rebuilding of earnings management based on Surah Al Muthaffifin in the Qur'an. This rebuilding model is meant to promote a religious and responsible attitude in the presentation of financial statements, reducing earnings management methods that can hurt connected parties